Using magnetic marketing tools to enhance the financial performance of the Iraqi general insurance company - Hamid, Zainab Rafid; Ibrahim, Maha Sabah (Edelweiss Applied Science and Technology, 2024)
The research aims to use magnetic marketing tools across its dimensions of (message, market, and media) to enhance the financial performance of the Iraqi General Insurance Company, as well as to identify the strengths and weaknesses in the company’s performance. Adopting the descriptive approach And Analytical Data and information were collected through the financial statements, annual reports and statistics of the company under study, relying on the annual reports issued by the Iraqi Insurance Bureau, as well as the performance evaluation indicators issued by the Federal Financial Supervision Bureau, represented by (the index of relative importance of insurance activity revenues, and production follow-up indicators) The fulfillment of plans, the development of production, the productivity of producers, the number of documents, and the loss rate) for the years (2018-2022). The research reached a set of results, the most important of which was that adopting magnetic marketing tools would enhance the revenues of insurance activity, reflected in the financial performance of the researched company.